Burn-injured adults with long term functional impairments demonstrate the same response to resistance training as uninjured controls - Grisbrook, Tiffany; Elliott, Catherine; Edgar, Dale; Wallman, K.; Wood, Fiona; Reid, S. (Pergamon, 2013)
Objective: The catabolic response associated with major burn injuries results in loss of lean body mass (LBM) and prolonged muscle weakness. Exercise training improves LBM and muscle strength in burn-injured children in the acute post injury phase, yet it is unknown whether adults will experience the same benefits when exercise training is implemented at least two years post injury.Procedures: Nine burn-injured participants (%TBSA = 42 18.38; time since injury = 6.56 3.68 years) and 9 matched controls participated in a 12-week interval training and resistance exercise programme. Muscle strength was assessed via isokinetic dynamometry and LBM was determined via dual energy X-ray absorptiometry. Both measures were administered prior to and following the exercise programme.Results: There was no significant difference in LBM or strength between the two groups at baseline. Following the exercise programme, both groups displayed significant improvements in LBM and in hip, shoulder and elbow muscle strength. There was no significant difference in muscle strength or LBM, between the groups, following the exercise training.Conclusion: A combined exercise training programme was able to improve muscle strength and lean body mass in adults with burn injury. There was no difference between the two groups in their response to the exercise programme, therefore general exercise prescription principles may be applied directly to the burns population.